Fermentation of seaweed flour with various fermenters to improve the quality of fish feed ingredients - Aslamyah, Siti; Karim, Muh Yusri; Badraeni, , (Indonesian Society of Scientific Aquaculture (ISSA), 2017)
ABSTRACT The purpose of this study was to evaluate various types of fermentor for dry matter digestibility (DMD), organic matter digestibility (OMD), and the chemical composition of fermented seaweed. Five types of seaweed were used as substrates included green strain of Kappaphycus alvarezii, brown strain of K. alvarezii, Gracilaria gigas, Sargassum sp., and Caulerpa sp. The treatments were four fermentors, namely Bacillus sp. 2 mL/100 g of seaweed flour; 1.5% of tape yeast as a source of Rhizopus sp.; 1.5% of baker’s yeast as a source of Saccharomyces sp.; a mix of Bacillus sp., tape yeast of Rhizopus sp. and baker’s yeast of Saccharomyces sp. with compositions of 1 mL+1 g+1 g/100 g of seaweed flour; and control treatment. The results showed an increase in the percentage of DMD (21.94–27.76%) and OMD (8.35–11.66%) of all seaweed fermented using fermentor compared to control (DMD of 17.65–20.36% and OMD of 4.36–5.98%). Moreover, the highest result was obtained by the fermentor mix (DMD of 24.86–27.76% and OMD of 10.02–11.66%). Similar result was also found in the chemical composition of fermented seaweed, there was increase in protein content of 9.23–15.93% and nitrogen free extract (NFE) of 56.05–70.26% in each seaweed treated with fermentation using fermentors, compared to controls (protein of 8.82–11.54% and NFE of 52.26–65.72%). Furthermore, the highest value was shown by seaweed fermented with mixed fermentors (protein of 9.92–15.93% and NFE of 58.47–70.26%). Yet, the opposite result was present in the ash, crude fiber, and fat content of seaweed fermented using fermentors of which the lowest value was found in treatment of mixed fermentor. Keywords: fermentation, fermentor, seaweed, quality, feed ingredients ABSTRAK Tujuan penelitian ini adalah mengevaluasi berbagai jenis fermentor terhadap kecernaan bahan kering (KBK), kecernaan bahan organik (KBO), dan komposisi kimia rumput laut terfermentasi. Lima jenis rumput laut digunakan sebagai substrat, yaitu Kappaphycus alvarezii strain hijau, K. alvarezii strain coklat, Gracillaria gigas, Sargasum sp., dan Caulerva sp. Perlakuan yang diuji empat fermentor, yaitu Bacillus sp. 2 mL/100 g tepung rumput laut; 1,5% ragi tape sebagai sumber Rhizopus sp.; 1,5% ragi roti sebagai sumber Saccharomyces sp.; campuran Bacillus sp., ragi tape Rhizopus sp., dan ragi roti Saccharomyces sp. dengan komposisi 1 mL+1 g+1 g/100 g tepung rumput laut; serta kontrol. Hasil penelitian menunjukkan terjadi peningkatan persentase KBK (21,94–27,76%) dan KBO (8,35–11,66%) semua jenis rumput laut difermentasi dengan fermentor dibandingkan kontrol (KBK 17,65–20,36, dan KBO 4,36–5,98%) dan yang tertinggi dengan fermentor campuran (KBK 24,86–27,76 dan KBO 10,02–11,66%). Begitu juga yang terjadi pada komposisi kimia rumput laut difermentasi, terjadi peningkatan kadar protein (9,23–15,93%) dan bahan ekstrak tanpa nitrogen/BETN (56,05–70,26%) pada setiap rumput laut yang diberi perlakuan fermentasi menggunakan fermentor, dibandingkan kontrol (protein 8,82–11,54% dan BETN 52,26–65,72%), yang tertinggi ditunjukkan oleh rumput laut yang difermentasi dengan fermentor campuran (protein 9,92–15,93% dan BETN 58,47–70,26%). Namun, terjadi sebaliknya pada kadar abu, serat kasar, dan lemak rumput laut yang difermentasi dengan fermentor lebih rendah dibandingkan kontrol, dan terendah dengan perlakuan fermentor campuran. Kata kunci: fermentasi, fermentor, rumput laut, kualitas, bahan pakan